2007
DOI: 10.1080/09602010701202154
|View full text |Cite
|
Sign up to set email alerts
|

Encephalitis in children: A clinical neuropsychology perspective

Abstract: Encephalitis is an inflammation of brain tissue that can result from a number of viruses and can be contracted at any age, with prevalence in children exceeding adult incidence. In order to illustrate specific cognitive, behavioural and service provision issues related to post-encephalitis rehabilitation of children, this paper examines the pattern of referrals to a specialist regional paediatric neuropsychology service in the United Kingdom. Three case vignettes are presented to demonstrate the wide range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is likely that poor cognitive, language, and motor outcomes will be linked to these variables. Vulnerable infants and young children likely are at the highest risk for morbidity and mortality (Starza-Smith et al, 2007).…”
Section: Anticipating a Neuropsychological Caseload Surgementioning
confidence: 99%
“…It is likely that poor cognitive, language, and motor outcomes will be linked to these variables. Vulnerable infants and young children likely are at the highest risk for morbidity and mortality (Starza-Smith et al, 2007).…”
Section: Anticipating a Neuropsychological Caseload Surgementioning
confidence: 99%
“…Physical symptoms may be evident on medical exam (e.g., fever, seizures), but dramatic behavioral changes may be important signs of an encephalitic condition (Ebaugh, 2007). In one study, an alarming 90% of infected children demonstrated "considerable" deficits in cognitive functioning, with 65% exhibiting moderate impairment in more specific executive functioning domains (Starza-Smith et al, 2007). Earlier age of infection has been associated with more severe and pervasive central nervous system (CnS) impairments (v. Anderson, Anderson, grimwood, & nolan, 2004).…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Epidemiological studies have suggested the incidence of encephalitis is about 16 cases per 100,000 children, with rates for some causes higher in developing countries (Starza-Smith, talbot, & grant, 2007). Encephalitis is typically caused by infection and subsequent brain tissue inflammation, so there are many causes.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Moreover, current knowledge about encephalitis is limited to descriptive statistics. As a result, a comprehensive understanding of human encephalitis, as generated through high quality evidence-based studies and statistical analyses is limited and much of the current knowledge base lacks generalizability [ 2 , 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%